Comparative analysis article “Romeo and Juliet” and “O‘tkan kunlar” (Journal of Science-Innovative Research in Uzbekistan, 2023)
"Romeo and Juliet" is a timeless tragedy written by William Shakespeare, exploring the ill-fated love story between two young individuals from feuding families. Set in Verona, Italy, the play follows the passionate and forbidden romance between Romeo Montague and Juliet Capulet, leading to a series of tragic events. Through poetic language, dramatic tension, and themes of love, fate, and societal constraints, Shakespeare's masterpiece captures the intensity and consequences of impulsive decisions driven by love